Exchange Interactions Drive Supramolecular Chiral Induction in Polyaniline. Issue 10 (20th September 2020) - Mishra, Suryakant; Kumar, Anup; Venkatesan, Munuswamy; Pigani, Laura; Pasquali, Luca; Fontanesi, Claudio
Abstract: The focus of this paper is on the intermolecular interaction active between polyaniline (PANI) and 10‐camphorsulfonic acid (10CSA). Enantiopure 10CSA, present in the electropolymerization solution, promotes chiral induction in the supramolecular polyaniline polymer (cPANI). Tight integration of experimental data (circular dichroism, CD, near edge X‐ray absorption spectra, NEXAFS, conductive probe atomic force microscopy, CP‐AFM) and theoretical [density functional theory, (DFT)] results allows to unfold the nature of the electronic interaction between PANI and 10CSA and to shed light on the physical interactions inducing the chiral character to bulk pristine non‐chiral PANI: eventually yielding cPANI. The electropolymerization follows a "wet chemistry" method: electrochemical polymerization of aniline in the co‐presence in bulk solution of enantiopure 10‐camphorsulfonic acid (10CSA). The latter is exploited as chirality inductor. The method of integration between experimental results with ab‐initio theoretical calculations, strongly suggests that the chiral induction exerted by the CSA stems from exchange interaction between CSA and PANI. Abstract : This work studies the camphor sulfonic acid induction of chirality on the supermolecular structure of electropolymerized aniline. The emergence of chirality is also associated to spin filtering properties of the chiral polymer, revealed by conducting probe Atomic Force Microscopy in the presence of a magnetic field. Theoretical results suggest that the chiral induction is due to exchange interaction energy.